Constant head permeameter formula dependence on the alpha parameter - HEMA R; Manoj Kurian; Raneesh K. Y; Er. V. M Abdul Hakkim (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
Constant head permeameter formula dependence on the alpha parameter
Constant head permeameter formula dependence on the alpha parameter